Testing an intervention of different learning activities to support students’ critical appraisal of scientific literature - Engelmann, Katharina; Hetmanek, Andreas; Neuhaus, Birgit J.; Fischer, Frank (Frontiers in Education, 2022)
In recent years the call for an evidence-based practice has become more prevalent for educational professionals. However, educational professionals are rarely prepared for evidence-based practice; for example, teachers are not prepared to use and, thus, rarely do use scientific evidence in planning lessons. The knowledge and skills in appraising scientific literature, the basis of evidence-based practice, needs to be trained as early in professional education as possible. An effective training might start in university education of future educational professionals, engaging them in learning activities that foster their understanding of criteria that are used in appraising scientific literature and the skill to do so. However, we know little about the effect of different learning activities such as constructive or interactive learning in this context. Thus, this study investigated the influence of constructive versus interactive learning activities in the context of an intervention facilitating knowledge and skills in appraising scientific literature. This experimental study used a pre-posttest between-subject design with 105 participants. The students learned to evaluate scientific literature in an online learning environment. The results show that the inclusion of interactive versus constructive learning activities did not explain students learning in the intervention. The results implicate that the learning activities might not play a major role with learning contents such as evidence-based practice. However, the gain in skills and knowledge from pre- to posttest shows promising achievements in preparing future educational professionals in their evidence-based practice.